(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Tonsillectomy with or without adenoidectomy is a commonly performed ENT operation over the world, also in our country. Though the operation takes less time and postoperative complication is uncommon but its postoperative complication specially the reactionary haemorrhage as well as secondary haemorrhage is life threatening which heralds immediate appropriate and adequate intervention. So, not only the meticulous surgical procedure rather each and every surgeon should not leave any stone unturned regarding preoperative, peroperative and postoperative care to prevent postoperative complication. More and more study regarding postoperative complication(s) of tonsillectomy or adenoidectomy or adenotonsillectomy operation should be carried out to increase awareness and consciousness among the ENT surgeons. Bangladesh J Otorhinolaryngol; April 2016; 22(1): 40-47